2004
DOI: 10.1081/ci-120028764
|View full text |Cite
|
Sign up to set email alerts
|

Application of Secondary Ion Mass Spectrometry to the Measurement of Lead Isotope Ratio in Individual Particles

Abstract: The capability of secondary ion mass spectrometry (SIMS) for lead isotope ratio measurements of individual particles has been demonstrated by measuring leadcontaining particles in three kinds of environmental certified reference materials (CRMs): urban particulate matter, vehicle exhaust particulates, and coal fly ash. After mounting of the sample onto a glassy carbon carrier, the particles containing lead were identified and located by an electron probe micro-analyzer equipped with wavelength dispersive x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Updates, numerous studies have been undertaken with secondary ion mass spectrometry (SIMS). Esaka et al 140 used SIMS to measure Pb isotope ratios of individual particles from three CRM: coal fly ash, vehicle exhaust particulate and urban particulates. Ratios were clearly distinguishable between the CRM and exhaust particulates could be separated into two groups by isotopic ratio.…”
Section: Other Mass Spectrometry Techniques As In Previousmentioning
confidence: 99%
“…Updates, numerous studies have been undertaken with secondary ion mass spectrometry (SIMS). Esaka et al 140 used SIMS to measure Pb isotope ratios of individual particles from three CRM: coal fly ash, vehicle exhaust particulate and urban particulates. Ratios were clearly distinguishable between the CRM and exhaust particulates could be separated into two groups by isotopic ratio.…”
Section: Other Mass Spectrometry Techniques As In Previousmentioning
confidence: 99%
“…With ever growing technique sophistication and the interest in the metal speciation contained within individual particulates, much more information can be gleaned. Esaka et al 78 demonstrated the capability of SIMS for measuring Pb isotope ratios in individual particles. Three kinds of environmental CRMs: urban particulate matter, vehicle exhaust particulates and coal fly ash were analysed.…”
Section: Petroleum Productsmentioning
confidence: 99%
“…Ion imaging revealed that these zones could be localized by using the Y 1 secondary ions. Esaka et al 308 used three RM to develop a method for the determination of Pb isotope ratios in mm-sized environmental particles. The samples were mounted on glassy carbon and Pb-containing particles, identified by EPXMA, were analysed using a 15 keV O 2 1 ion beam (spot diameter of 50 mm), a mass resolution of 1000 and energy filtering to discriminate against hydride contributions.…”
Section: Quantitative Analysismentioning
confidence: 99%